Smart Waste Management Monitoring and Control Analysis Based on Objects Based on Smart Systems and Internet of Things - Sarmila, Sarmila; Achmad, Andani; Arda, Abdul Latief (Politeknik Negeri Batam, 2025)
Garbage is a problem that often becomes a trending topic in almost every country.throughout developing countries. The current condition of waste in our environment is still in a mixed condition, because the garbage has not been sorted. The minimum waste management information technology by officers also causes Waste management is slow, so that waste often piles up.The aim of this research is to develop a smart trash can that can sort metal, dry and wet waste automatically via Internet function of Things (IoT). The methodology used is Research and Development which can provide information when the trash can is full. This research was successful designing and implementing a prototype of a smart trash can based onInternet of Things (IoT) with the ability to sort waste into three categories The main components are metal, wet, and dry. The system utilizes proximity sensors inductive, soil sensor, and ultrasonic sensor HC-SR04 integrated with Blynk application for real-time monitoring of waste capacity. Algorithm Fuzzy logic is used so that the system is able to make adaptive decisions according to with the sensor condition. from the performance in the research Where the Accuracy of the system is 97.10%. The calculation is based on the number of correct predictions on the diagonal. main data divided by total data: true = 189 (Dry) + 187 (Wet) + 194 (Metal) = 570 out of a total of 587 samples, so 570/587 = 0.9710 (97.10%), with 17 error (error rate 2.90%). These values describe how much the accuracy and completeness of the model in recognizing each category of waste, with results consistently high (average 0.97).